2001
DOI: 10.1164/ajrccm.164.3.2009042
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic Examination

Abstract: We evaluated ultrasonic examination as a diagnostic tool for catheter misplacement and pneumothorax after central venous catheter insertion. Physicians in the intensive care unit (ICU) performed the ultrasonic examinations, and the results were compared with those of chest radiography. Eighty-five central venous catheters (70 subclavian and 15 internal jugular) were inserted into 81 patients; 10 misplacements and one pneumothorax occurred. Ultrasonic examination feasibility was 99.6%. The only pneumothorax and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(44 citation statements)
references
References 18 publications
0
43
0
1
Order By: Relevance
“…Some of these studies described ultrasonography as an accurate method for identifying catheter location and avoiding life-threatening complications, such as pneumothorax (12-15, 17-19). Maury and colleagues reported a high success rate of ultrasonic evaluation in detecting aberrant catheter location and pneumothorax (14). Vezzani and colleagues compared chest radiography with a combination of B-mode ultrasonography and CEUS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these studies described ultrasonography as an accurate method for identifying catheter location and avoiding life-threatening complications, such as pneumothorax (12-15, 17-19). Maury and colleagues reported a high success rate of ultrasonic evaluation in detecting aberrant catheter location and pneumothorax (14). Vezzani and colleagues compared chest radiography with a combination of B-mode ultrasonography and CEUS.…”
Section: Discussionmentioning
confidence: 99%
“…Post-procedure chest radiography is the main method of verifying catheter location. Despite the widespread use of this method, it is time-consuming and it exposes patients to high levels of radiation (12-14). In addition, the feasibility of immediate post-procedure radiography is controversial.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the time required for ultrasound examination was much shorter (6.8 ± 3.5 min) [8]. A prior evaluation in our institution showed that the median processing time was 20 min and ranged from 5 min to 25 min.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that ultrasound can detect the absence of complications and the correct positioning of the catheter and can reduce the processing time of the audit report on chest radiographs [8,22]. The standard deviation of the processing time varies between 5 min and 25 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation